Determination of butyric acid dosage based on clinical and experimental studies – a literature review - Tomasz Banasiewicz; Dorota Domagalska; Katarzyna Borycka-Kiciak; Grażyna Rydzewska (Gastroenterology Review)
Short-chain fatty acids produced by bacteria living in the large intestine are the main energy substrate for the colonocytes. Butyric acid is used for the treatment and prevention of exacerbations of various gastrointestinal diseases: diarrhoea, intestinal inflammations, functional disorders, dysbiosis, and post-surgery or post-chemotherapy conditions. The current standard doses of butyric acid (150–300 mg) range between 1.5–3% and 15–30% of the reported daily demand. Increased metabolism of the colonocytes in conditions involving intestine damage or inflammation, increased energy expenditure during a disease, stimulation of intestine growth in ‘stress’ conditions with accelerated intestinal passage and increased intestinal excretion, and decreased production of endogenous butyrate due to changes in bacterial flora in different pathological conditions require a significant increase of the supply of this acid. Physiological high demand for butyrate and known mechanisms of pathological conditions indicate that current supplementation doses do not cover the demand and their increase should be considered.